Efektivitas Terapi Kognitif Perilakuan untuk Meningkatkan Efikasi Diri Abstinen NAPZA - Erga Patragave Ratih; Muhana Sofiati Utami (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
The research aimed to determine the effectiveness of Cognitive-Behavior Therapy to increase self-efficacy towards multiple drug addicts. The One-Group Pretest-Posttest Design was used in the research. The participants were 6 people who were the resident of Drug Rehabilitation Center “K” located in Sleman, Special Region of Yogyakarta. Pretest and posttest measure by Drug Avoidance Self-Efficacy Scale. Data were analyzed by non-parametric statistics, used Wilcoxon analysis. The results showed a significance of 0.0135. According to the results, there was an indication that Cognitive-Behavior Therapy’s module was able to increase self-efficacy among drug addicts.